Technological options for improving the wear resistance of the knives of the chopping drum of the combine by electrical contact welding of coatings - Дудан, О.В.; Cолових, Є.К.; Волков, Ю.В.; Катеринич, С.Є.; Солових, А.Є.; Шевченко, Д.В. (Problems of Tribology, 2019)
On the basis of the studies conducted, it was determined that among the methods of applying coatings, preference should be given to the method of electrocontact welding, which uses thermal energy emitted by electric current. Electrocontact powder coating is characterized by low energy consumption, a small heat-affected zone, high performance, adhesion strength and density. The reason for the wear of traditional coatings is their local overstrain. In order to eliminate this drawback, it was proposed to apply a coating not solid, but discrete. The coating of a discrete structure by electrocontact welding allows, along with high density and adhesive strength, to ensure a minimum level of stress-strain state of the coating under the influence of operating loads. Simulation of the coatings of a discrete structure during electrocontact sintering allowed choosing the geometrical parameters of a discrete surface, material and optimal coating application modes. On the basis of experimental studies and using mathematical modeling comprehensive assessment of the impact of major technological parameters (pressure, current, speed of sintering) of the electrocontact sintering process of powders on physical and mechanical properties of the coatings (adhesion strength and durability) is given. Multivariate experiment with a certain variation of these parameters allowed us to estimate the impact of each of them on the properties of the coatings and to identify the effects of the interaction. It is concluded that in order to improve the physical and mechanical properties of the resulting coatings is advisable to use all three complex technological parameters of the process.